HUBUNGAN PEMANFAATAN TEKNOLOGI INFORMASI DAN MOTIVASI BELAJAR DENGAN PRESTASI BELAJAR IPS SISWA SMPN DI KABUPATEN TAPIN - Sriyanti Sriyanti (Universitas Lambung Mangkurat, 2014)
This study is an ex-post facto, with a population of 1,045 students. Research sample of 204 students, which is determined by random cluster sampling technique. To determine the minimum sample size used Solvin formulas. The results showed that most of the students of SMPN in Tapin district has been using information technology in learning IPS that as many as 127 respondents (62.25%) in the medium category. Use of information technology is used as a media / learning aids (57.35%) and as a learning resource (68.63%). Student motivation in the category were as many as 140 students (68.63%) and the achievement of social studies are also in the category of being a total of 143 students (70.10%). The analysis showed that there is a significant relationship between the use of information technology and the learning achievement IPS (r = 0.752, p <0.05), between the students' motivation and academic achievement IPS (r = 0.604, p <0.05) and collectively cooperation between the utilization of information technology and student motivation and academic achievement IPS (r12y = 0.691, p <0.05).Keywords: Utilization of Information Technology, Learning Motivation, Achievement IPS